(untitled) (Research, Society and Development, 2020)
The use of didactic-pedagogical tools alternative to the blackboard and chalk, including virtual learning objects, contribute to a teaching strategy that facilitates the teaching and learning process in chemistry. Gamification has proved to be an important strategy to strengthen student engagement. In this context, the objective of this work was the development and application of an escape game, called EscapeLab where the character moves through the game environments solving puzzles related to chemistry content, in order to stimulate the user’s learning. The game was applied to a high school class. In addition to a qualitative research, a pre-test and a post-test were applied to analyze the content assimilated by students after using this didactic-pedagogical tool. It was observed that EscapeLab was well accepted by students and helped to assimilate chemical concepts. Works of this nature contribute significantly to society as they enable digital inclusion and are based on the awakening of interest in science, through the unification of study and fun, using the virtual games that are so present in the daily lives of these young people. Based on constructivist pedagogical ideas built on the ideas of Jean Piaget, it can be concluded that an educational game, properly selected and monitored by an apt teacher, is an excellent pedagogical tool.